The Impact of Greenwashing Advertising on Consumer Behavior - Dewi, Patricia Citra; Tarina, Dwi Desi Yayi (Magister Ilmu Hukum Fakultas Hukum Universitas 17 Agustus 1945 Surabaya, 2024)
The economic motive of businesses in manipulating environmental aspects in increasing sales turnover so that consumers feel harmed by the advertising information. Greenwashing has significant negative impacts, both for consumers and companies that are truly committed to sustainability. For consumers, greenwashing can lead to misinformation and inappropriate purchasing decisions. Consumers who feel deceived by false environmental claims may experience disillusionment and lose trust in environmental claims as a whole. This can also be detrimental to companies that truly strive to carry out sustainable business practices, as it is difficult to differentiate themselves from companies that only pretend to care about the environment. This study aims to analyze theimpact of advertising greenwashing on consumer behavior. Methode in this research used yuridis normative with conceptual approach and legislation approach related to consumer protection and mediaenvironmentally friendly campaigns on goods and/or services. The results of this study indicate that rregulations related to consumer protection have not specifically regulated the concept of greenwashing, but have regulated the rights and obligations of business actors related to the act of greenwashing which mis leads to consumer decision making. Acts of greenwashing committed by business actors have violated consumer rights relating to correct and clear information and not misleading about the condition of goods and/or services traded. Business actors must be responsible in terms of withdrawing these advertisements and/or must be prepared to take responsibility for the resulting impact on consumers and/or the environment.